The Influence of the PjBL Model with the STEAM Approach on the Creative Thinking Ability and Mathematical Learning Motivation - Evina Triagustina; Dwi Andriyani; Wida Susanti; Anisa Nur Sabiila; Gunawan Gunawan (Universitas Muhammadiyah Mataram, 2026)
Learning mathematics in the 21st century requires students to develop creative thinking skills and strong learning motivation. However, these aspects remain relatively low because mathematics instruction is often procedural and lacks contextual learning experiences. Therefore, innovative learning approaches that integrate both cognitive and affective dimensions are needed. This study aimed to examine the effect of the Project-Based Learning (PjBL) model integrated with the STEAM approach on students’ creative thinking ability and mathematics learning motivation. This study employed a quantitative approach with a quasi-experimental pretest-posttest control group design. The participants consisted of 54 eighth-grade students selected through cluster random sampling, with 27 students assigned to the experimental class and 27 students to the control class. The research instruments included a mathematical creative thinking test and a mathematics learning motivation questionnaire. Data were analyzed using Multivariate Analysis of Covariance (MANCOVA) and Pearson Product-Moment correlation at a significance level of 0.05. The findings revealed that the STEAM-based PjBL model significantly affected students’ creative thinking ability and learning motivation simultaneously (p < 0.05). The multivariate test also demonstrated a very large practical effect, as indicated by the partial eta squared value (ηp² = 0.966). Furthermore, the correlation analysis showed a very strong positive relationship between creative thinking ability and learning motivation (r = 0.885; p < 0.05). These findings indicate that STEAM-integrated project-based learning creates contextual, interactive, and meaningful learning experiences that support both cognitive and affective development. Therefore, the STEAM-based PjBL model can be considered an effective and innovative alternative for fostering 21st-century skills in mathematics learning.